The Lord of the rings sketchbook - Lee, Alan (Houghton Mifflin, 2005)
"The book is filled with more than 150 of his sketches and early conceptual pieces showing how the project progressed from idea to finished art. It also contains a selection of full-page paintings reproduced in full color, together with numerous examples of previously unseen conceptual art produced for the films and many new works drawn specially for this book. The lord of the ring sketchbook provides a fascinating insight into the imagination of the man who painted Tolkien's vision, first on the page and then in three dimensions on the movie screen. It will also be of interest to many of the thousands of people who have bought the illustrated Lord of the Rings as well as to budding artists who want to unlock the secrets of book illustration." -- Provided by publisher